2006
DOI: 10.1182/blood-2006-04-016360
|View full text |Cite
|
Sign up to set email alerts
|

Circulating proteasome levels are an independent prognostic factor for survival in multiple myeloma

Abstract: The proteasome is a proteolytic complex for intracellular degradation of ubiquitinated proteins which are involved in cellcycle regulation and apoptosis. A constitutively increased proteasome activity has been found in myeloma cells. We studied circulating proteasome levels and their prognostic significance in sera of 50 control subjects, 20 persons with monoclonal gammopathies of undetermined significance (MGUS), and 141 previously untreated patients with multiple myeloma (MM) by an anti-20S proteasome enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 46 publications
7
95
1
4
Order By: Relevance
“…Circulating proteasome levels were found to be an independent prognostic factor for survival in previously untreated patients with multiple myeloma. 30 Bortezomib (PS-341), 31 that is the first proteasome inhibitor approved by the Food and Drug Administration, was shown to induce the stabilization of I-kB, 32 c-Fos and c-Jun. 33,34 In multiple myeloma, the major effects of bortezomib were contributed to the inhibition of NF-kB activation.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating proteasome levels were found to be an independent prognostic factor for survival in previously untreated patients with multiple myeloma. 30 Bortezomib (PS-341), 31 that is the first proteasome inhibitor approved by the Food and Drug Administration, was shown to induce the stabilization of I-kB, 32 c-Fos and c-Jun. 33,34 In multiple myeloma, the major effects of bortezomib were contributed to the inhibition of NF-kB activation.…”
Section: Introductionmentioning
confidence: 99%
“…Bortezomib is used in the treatment of multiple myeloma (Fisher et al, 2006). Notably, multiple myeloma has been observed to result in increased proteasome levels in blood serum that decrease to normal levels in response to successful chemotherapy (Jakob et al, 2007). Studies in animals have indicated that bortezomib may also have clinically significant effects in pancreatic cancer (Nawrocki et al, 2004;Shah et al, 2001).…”
Section: Proteasomementioning
confidence: 99%
“…Proteasomes are highly expressed in transformed cells contributing to the aggressive growth of cancer cells. 25,26 Though this mechanism is incompletely understood, it seems to involve the rapid degradation of cell cycle and pro-apoptotic proteins, mediated primarily through the destabilization of TP53 and NFκB (reviewed in ref. 27).…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%